Nano-structure thermal protection coating resistant to long-time high-temperature oxidation and preparation method of nano-structure thermal protection coating
By introducing self-healing components and Re2Si2O7 composite powder into the environmental barrier coating, using a double-layer coating structure and thermal spraying technology, the stability and phase transition problems of the coating in a long-term service environment are solved, and higher high-temperature stability and hot and cold cycle life are achieved.
Patent Information
- Application Number
- CN202510037128.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-09
AI Technical Summary
The existing environmental barrier coatings have poor stability in high temperature and long service environments, and are prone to phase change during the spraying process, mismatch between layers of thermal expansion and poor cold and heat circulation performance, resulting in the failure of the coating service.
Through self-healing and synthetic components composite, self-healing additive/Re2Si2O7 sprayable powder is prepared by spray granulation method, and the double-layer coating structure is constructed using thermal spraying technology to solve the phase change problem of silicate spraying process.
The high-temperature phase stability of the coating is achieved, matching the thermal expansion coefficient of the silicon-based ceramic matrix, suppressing phase change during spraying, and improving the long-term stable service performance and hot and cold cycle life of high temperatures.
Smart Images

Figure CN119797917A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a high-temperature thermal protective coating and a preparation method thereof, and in particular to a nanostructured thermal protective coating resistant to long-term high-temperature oxidation and a preparation method thereof. Background Art
[0002] With the continuous development of the aerospace and marine industries, the operating temperatures of engines and gas turbines are increasing, and traditional nickel-based high-temperature alloys can no longer meet future service requirements. Ceramic-based composite materials, represented by silicon-based structural ceramic materials, are considered to be the most promising materials for engine hot end components to replace nickel-based high-temperature alloys due to their light weight and good high-temperature mechanical properties. However, ceramic-based composite materials are easily corroded by environmental media in service environments, causing the material to fail rapidly. Environmental barrier coatings have been proposed as an important barrier to protect ceramic-based composite materials from environmental media corrosion.
[0003] With the continuous development of environmental barrier coatings, rare earth silicate materials have attracted extensive attention from researchers due to their low thermal conductivity, good resistance to water-oxygen corrosion and molten salt corrosion, and excellent stability in the high-temperature airflow working environment of the engine. Atmospheric plasma, as the most widely used spraying method at present, will cause silicate decomposition and phase change during the preparation of silicate coatings. Due to the multiple temperature cycles in the service process, cracks are likely to occur during use, and thermal oxide growth will occur, which will lead to thermal stress accumulation and ultimately vertical crack relaxation, resulting in a short service life. Summary of the invention
[0004] In view of the problems of poor stability in long-term service at high temperature, easy phase change during the spraying process, mismatched thermal expansion between layers, and poor cold and hot cycle performance in existing environmental barrier coatings, which lead to coating service failure, the present invention provides a nanostructured thermal protective coating resistant to long-term high-temperature oxidation and a preparation method thereof. From the perspective of raw material design, the method is compounded with self-healing components on existing commonly used double silicate materials, and a self-healing additive (Selfhealing additive) / Re2Si2O7 sprayable powder is prepared by spray granulation. A self-healing component / silicate composite coating is constructed by thermal spraying technology, and a double-layer coating structure is used to replace the current three-layer environmental barrier coating system, which successfully solves the phase change problem of silicate spraying process. The coating prepared by the present invention has good high-temperature phase stability, a thermal expansion coefficient that is more matched with the silicon-based structural ceramic matrix, and can effectively inhibit the phase change generated during the spraying process, and has higher high-temperature long-term stable service performance and cold and hot cycle life.
[0005] The objective of the present invention is achieved through the following technical solutions:
[0006] A self-healing additive / Re2Si2O7 sprayable powder is prepared by spray granulation using a self-healing additive and Re2Si2O7 as main raw materials, wherein:
[0007] The self-healing additive is one or more of Si, MoSi2, SiC, TiC, and Al2O3;
[0008] The content of the self-healing additive is 1 to 60% of the total mass of the sprayable powder;
[0009] In the Re2Si2O7, Re is one or more of Y, Yb, Lu, Er, and Sc.
[0010] A method for preparing the above-mentioned self-healing additive / Re2Si2O7 sprayable powder comprises the following steps:
[0011] Step 1: Add deionized water to the ball mill, then add dispersant to the deionized water, and after the dispersant is completely dissolved, add nano Re2O3 powder, nano SiO2 powder and self-healing additive according to the designed ratio of Re2Si2O7 and the content of self-healing additive, and then ball mill for 6 to 24 hours, then add binder and continue ball milling for 0.5 to 2 hours to obtain a uniform slurry, wherein:
[0012] The particle size of the nano Re2O3 powder and nano SiO2 powder is 5-60nm, with 4N grade purity;
[0013] The dispersant is sodium tripolyphosphate (Na5P3O 10 )、Sodium hexametaphosphate ((NaPO3)6)、Ammonium citrate (C6H5O7(NH4)3)、Sodium citrate (C6H5Na3O7) 、 One or more of methyl amyl alcohol (C6HO), polyacrylamide (PAM), etc., the amount of the dispersant is 0.03-4% of the total mass of the sprayable powder;
[0014] The binder is one of gum arabic (Acacia), polyvinyl alcohol (PVA), polyethylene glycol (PEG), epoxy resin, etc., and the amount of the binder is 0.02-15% of the total mass of the sprayable powder;
[0015] Step 2: After spray granulation and solid phase sintering, the uniform slurry is obtained into spherical powder, wherein:
[0016] The solid phase sintering is carried out in a protective atmosphere environment, and the protective atmosphere can be one or more of nitrogen, argon, and helium;
[0017] The solid phase sintering conditions are: firstly heating to 350°C at a rate of 2-15°C / min and keeping the temperature for 1-4h, then heating to 1100-1600°C at a rate of 5-20°C / min and keeping the temperature for 0.5-4h;
[0018] The particle size of the spherical powder is 25 to 100 μm;
[0019] The spherical powder is a nanostructured self-healing additive / Re2Si2O7 powder.
[0020] A nanostructured thermal protective coating resistant to long-term high-temperature oxidation, with a ceramic-based composite material as a matrix, and a bonding layer and a composite component coating sprayed on the surface of the matrix in sequence, wherein:
[0021] The ceramic matrix composite material is one of silicon carbide structural ceramics and silicon nitride structural ceramics;
[0022] The material of the bonding layer is one or more materials selected from Si, SiC, SiN, MoSi2, Si-HfO2, MoSi2-HfO2, and HfSiO4;
[0023] The thickness of the bonding layer is 50 to 150 μm;
[0024] The material of the composite component coating is a self-healing additive / Re2Si2O7 sprayable powder;
[0025] The thickness of the composite component coating is 80 to 350 μm.
[0026] A method for preparing the above-mentioned nanostructured thermal protective coating resistant to long-term high-temperature oxidation, such as Figure 1 As shown, the following steps are included:
[0027] Step 1: Using a spray granulation method, nanostructured self-healing additive / Re2Si2O7 spherical powders with different rare earth elements and different self-healing additive contents are prepared:
[0028] Step 1: Add deionized water to the ball mill, then add dispersant to the deionized water, and after the dispersant is completely dissolved, add nano Re2O3 powder, nano SiO2 powder and self-healing additive according to the designed ratio of Re2Si2O7 and the content of self-healing additive, and ball mill for 6 to 24 hours, then add binder and continue ball milling for 0.5 to 2 hours to obtain a uniform slurry, wherein:
[0029] The self-healing additive is one or more of Si, MoSi2, SiC, TiC, and Al2O3;
[0030] The content of the self-healing additive is 1 to 60% of the total mass of the sprayable powder;
[0031] In the Re2Si2O7, Re is one or more of Y, Yb, Lu, Er, and Sc;
[0032] The particle size of the nano Re2O3 powder and nano SiO2 powder is 5-60nm, with 4N grade purity;
[0033] The dispersant is sodium tripolyphosphate (Na5P3O 10 )、Sodium hexametaphosphate ((NaPO3)6)、Ammonium citrate (C6H5O7(NH4)3)、Sodium citrate (C6H5Na3O7) 、 One or more of methyl amyl alcohol (C6HO), polyacrylamide (PAM), etc., the amount of dispersant is 0.03-4% of the total mass of the sprayable powder;
[0034] The binder is one of gum arabic (Acacia), polyvinyl alcohol (PVA), polyethylene glycol (PEG), epoxy resin, etc., and the amount of the binder is 0.02-15% of the total mass of the sprayable powder;
[0035] Step 1 and 2: After spray granulation and solid phase sintering, the uniform slurry is obtained into spherical powder, wherein:
[0036] The solid phase sintering is carried out in a protective atmosphere environment, and the protective atmosphere can be one or more of nitrogen, argon, and helium;
[0037] The solid phase sintering conditions are: firstly heating to 350°C at a rate of 2-15°C / min and keeping the temperature for 1-4h, then heating to 1100-1600°C at a rate of 5-20°C / min and keeping the temperature for 0.5-4h;
[0038] The particle size of the spherical powder is 25 to 100 μm;
[0039] The spherical powder is a nanostructured self-healing additive / Re2Si2O7 spherical powder;
[0040] Step 2: Using the ceramic-based composite material as the substrate, grinding and polishing the surface to make it smooth and then roughening it to prepare a certain degree of roughness on the surface, and then using ethanol and acetone to ultrasonically clean it respectively, and after drying, using thermal spraying technology to prepare a bonding layer on its surface, wherein:
[0041] The roughening treatment includes one or more of sandblasting, femtosecond laser processing and surface chemical etching;
[0042] The thermal spraying technology is one of atmospheric plasma spraying (APS), low pressure plasma spraying (LPPS), and high velocity oxygen fuel (HVOF);
[0043] When the bonding layer is prepared by atmospheric plasma spraying, the preparation parameters are: spraying distance is 7-250 mm, powder feeding rate is 8-25 g / min, carrier gas flow rate is 3-14 SCFH, spraying current is 450-700 A, spraying voltage is 40-70 V, main gas flow rate is 25-70 SCFH, auxiliary gas flow rate is 2-18 SCFH, and spraying speed is 10-40 mm / s;
[0044] When the bonding layer is prepared by supersonic flame spraying, the preparation parameters are: spraying distance is 150-500 mm, powder feeding rate is 10-50 g / min, carrier gas flow rate is 1-8 NLPM, shielding gas flow rate is 150-550 NLPM, fuel flow rate is 80-350 NLPM, oxygen flow rate is 100-400 NLPM, and spraying speed is 20-110 mm / s;
[0045] Step 3: Using atmospheric plasma spraying (APS) technology, the nanostructured self-healing additive / Re2Si2O7 spherical powder obtained in step 1 is deposited on the surface of the bonding layer obtained in step 2 to form a composite component coating, thereby obtaining a thermal protective coating with a nanostructure, good high-temperature phase stability, a thermal expansion coefficient that is more matched with the silicon-based ceramic matrix, and phase stability maintained during the spraying process, wherein:
[0046] The preparation parameters of the composite component coating are: spraying distance of 60-350 mm, powder feeding rate of 5-30 g / min, carrier gas flow rate of 4-165 CFH, spraying current of 400-800 A, spraying voltage of 45-80 V, main gas flow rate of 15-70 SCFH, and auxiliary gas flow rate of 3-20 SCFH.
[0047] Compared with the prior art, the present invention has the following advantages:
[0048] 1. The present invention utilizes nano powder regranulation technology to prepare Selfhealing additive / Re2Si2O7 into nano structured spherical powder suitable for thermal spraying for the first time, providing a method for implementing the high performance material on thermal spray nano structured coating.
[0049] 2. The present invention uses APS technology for the first time to prepare nanostructured Selfhealing additive / Re2Si2O7 thermal protective coating. This technology has the advantages of high energy, wide range of material applications, easy operation, high deposition efficiency, and easy industrialization.
[0050] 3. The coating prepared by the present invention has a typical multimodal structure, that is, there are completely melted, partially melted and unmelted particles, and the porosity is 4 to 13%. The large number of defects in the coating can increase phonon and photon scattering, thereby reducing the thermal conductivity of the coating, while relieving the internal stress of the coating and improving the service life of the coating.
[0051] 4. The coating prepared by the present invention has a stable phase structure at high temperature, the powder does not undergo phase change during the spraying process, and has a good thermal expansion coefficient matching with the substrate, which significantly improves the service life of existing environmental barrier coatings and has broad prospects for use. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 A process flow chart for preparing a nanostructured thermal protection coating resistant to long-term high-temperature oxidation;
[0053] Figure 2 The surface morphology of the coating after adding different amounts of self-healing components;
[0054] Figure 3 The cross-sectional morphology of the coating after adding different amounts of self-healing components;
[0055] Figure 4 XRD patterns of the deposited coatings with different self-healing component addition contents. DETAILED DESCRIPTION
[0056] The technical solution of the present invention is further described below in conjunction with the embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.
[0057] Embodiment 1:
[0058] This embodiment provides a method for preparing a nanostructured thermal protection coating resistant to long-term high-temperature oxidation, and the method is achieved by the following steps:
[0059] Step 1: Add deionized water to the ball mill, then add dispersant ammonium citrate to the deionized water, and after the dispersant ammonium citrate is completely dissolved, add nano Yb2O3 powder, nano SiO2 powder, self-healing additive SiC nano powder and 5mm zirconium oxide ball milling balls. After ball milling for 8 hours, add binder PVA and continue ball milling for 0.5 hours to obtain a uniform slurry, wherein: the amount of SiC nano powder is 10% of the total mass of the sprayable powder, the amount of ammonium citrate is The amount of PVA is 0.7% of the total mass of the sprayable powder, the amount of PVA is 0.5% of the total mass of the sprayable powder, the mass ratio of deionized water to the sprayable powder is 1:1, and the amount of zirconia ball milling balls is twice the total mass of the sprayable powder; the uniform slurry is spray granulated and solid-phase sintered to obtain a sprayable composite component powder, and the conditions of solid-phase sintering are: in an argon protective atmosphere furnace, first increase the temperature to 350°C at a rate of 5°C / min and keep it for 2h, then increase the temperature to 1200°C at a rate of 10°C / min and keep it for 1h.
[0060] Step 2: Use 80-320 mesh silicon carbide sandpaper to sand the SiC f After the surface of the SiC substrate was polished, the substrate surface was sandblasted with 60-mesh white corundum to give it a certain surface roughness. Then, it was ultrasonically cleaned for 15 minutes with anhydrous ethanol and acetone respectively to obtain a substrate with a certain surface roughness.
[0061] Step 3: Prepare a Si-HfO2 bonding layer on the substrate surface by atmospheric plasma spraying technology. The preparation parameters of the bonding layer are: spraying distance is 110 mm, powder feeding rate is 16 g / min, carrier gas flow rate is 10 SCFH, spraying current is 570 A, spraying voltage is 57 V, main gas flow rate is 48 SCFH, auxiliary gas flow rate is 12 SCFH, and the thickness of the bonding layer is 100 μm.
[0062] Step 4: Deposit the sprayable composite component powder obtained in step 1 on the surface of the bonding layer prepared in step 3 by atmospheric plasma spraying to obtain a double-layer composite component ceramic coating. The preparation parameters of the composite component coating are: spraying distance of 120 mm, powder feeding rate of 20.0 g / min, carrier gas flow rate of 11 SCFH, spraying current of 720 A, spraying voltage of 72 V, main gas flow rate of 50 SCFH, auxiliary gas flow rate of 10 SCFH, and ceramic layer thickness of 150 μm.
[0063] The surface morphology of the coating prepared in this example is as follows Figure 2 As shown in c) and d), the overall cladding effect of the coating is good. As the self-healing component increases, the rice-like submicrostructure on the coating surface increases. The cross-sectional morphology of the coating is as follows: Figure 3As shown in d), e), and f), the overall thickness of the coating remains uniform, the interface is tortuous and enhances the locking effect, the elements are evenly distributed, and no phase change occurs. As the self-healing component increases, the submicron pores in the coating increase, which can increase the strain tolerance of the coating; the XRD spectrum of the coating is shown in Figure 4 As shown, the coating surface layer did not undergo phase change decomposition; the coating resisted 1000 hot and cold cycles at 1400°C without falling off, and did not fall off after 2000h of thermal oxidation at 1400°C.
[0064] Embodiment 2:
[0065] This embodiment provides a method for preparing a nanostructured thermal protection coating resistant to long-term high-temperature oxidation, and the method is achieved by the following steps:
[0066] Step 1: Add deionized water to the ball mill, then add dispersant sodium hexametaphosphate to the deionized water, and after the dispersant sodium hexametaphosphate is completely dissolved, add nano Lu2O3 powder, nano SiO2 powder, self-healing additive MoSi2 nano powder and 3mm zirconium oxide ball milling balls. After ball milling for 10 hours, add binder PVA and continue ball milling for 0.5 hours to obtain a uniform slurry, wherein: the amount of MoSi2 nano powder is 15% of the total mass of the sprayable powder, and sodium hexametaphosphate is 15% of the total mass of the sprayable powder. The amount of PVA is 1% of the total mass of the sprayable powder, the amount of deionized water is 0.5% of the total mass of the sprayable powder, the mass ratio of deionized water to sprayable powder is 1.5:1, and the amount of zirconia ball milling balls is 3 times the total mass of the sprayable powder; the uniform slurry is spray granulated and solid-phase sintered to obtain a sprayable composite component powder. The conditions for solid-phase sintering are: in a vacuum muffle furnace, first increase the temperature to 350°C at a rate of 4°C / min and keep it for 1h, then increase the temperature to 1300°C at a rate of 8°C / min and keep it for 2h.
[0067] Step 2: Use 80-320 mesh silicon carbide sandpaper to sand the C f After the surface of the SiC substrate was polished, the substrate surface was sandblasted with 60-mesh white corundum to give it a certain surface roughness. Then, it was ultrasonically cleaned for 30 minutes with anhydrous ethanol and acetone respectively to obtain a substrate with a certain surface roughness.
[0068] Step 3: Prepare a Si bonding layer on the substrate surface by atmospheric plasma spraying technology. The bonding layer preparation parameters are: spraying distance is 100 mm, powder feeding rate is 12 g / min, carrier gas flow rate is 8 SCFH, spraying current is 530 A, spraying voltage is 53 V, main gas flow rate is 45 SCFH, auxiliary gas flow rate is 10 SCFH, and the thickness of the bonding layer is 150 μm.
[0069] Step 4: Deposit the sprayable composite component powder obtained in step 1 on the surface of the bonding layer prepared in step 3 by atmospheric plasma spraying to obtain a double-layer composite component ceramic coating. The preparation parameters of the composite component coating are: spraying distance of 110 mm, powder feeding rate of 13.0 g / min, carrier gas flow rate of 10 SCFH, spraying current of 740 A, spraying voltage of 74 V, main gas flow rate of 55 SCFH, auxiliary gas flow rate of 14 SCFH, and ceramic layer thickness of 170 μm.
[0070] Embodiment 3:
[0071] This embodiment provides a method for preparing a nanostructured thermal protection coating resistant to long-term high-temperature oxidation, and the method is achieved by the following steps:
[0072] Step 1: Add deionized water to the ball mill, then add dispersant sodium citrate to the deionized water, and after the dispersant sodium citrate is completely dissolved, add nano Sc2O3 powder, nano SiO2 powder, self-healing additive TiC nano powder and 3mm zirconium oxide ball milling balls. After ball milling for 7 hours, add the binder gum arabic and continue ball milling for 0.5 hours to obtain a uniform slurry, wherein: the amount of the TiC nano powder is 10% of the total mass of the sprayable powder, the amount of the sodium citrate is The amount of gum arabic is 0.5% of the total mass of the sprayable powder, the mass ratio of deionized water to sprayable powder is 3:1, and the amount of zirconia ball milling balls is 2.5 times the total mass of the sprayable powder; the uniform slurry is spray granulated and solid-phase sintered to obtain a sprayable composite component powder, and the conditions for solid-phase sintering are: in a helium protective atmosphere furnace, first increase the temperature to 350°C at a rate of 3°C / min and keep it for 2h, then increase the temperature to 1400°C at a rate of 10°C / min and keep it for 1.5h.
[0073] Step 2: Use 80-320 mesh silicon carbide sandpaper to sand the C f After the surface of the SiC substrate was polished and finished, the substrate surface was sandblasted with 60-mesh white corundum to give it a certain surface roughness. Then, it was ultrasonically cleaned with anhydrous ethanol and acetone for 20 minutes respectively to obtain a substrate with a certain surface roughness.
[0074] Step 3: Prepare a Si bonding layer on the substrate surface using supersonic plasma spraying technology (HVOF). The bonding layer preparation parameters are: spraying distance 350 mm, powder feeding rate 30 g / min, oxygen flow rate 1400 SLPM, kerosene flow rate 20 / h, spray gun moving speed 750 mm / s, and the thickness of the bonding layer is 140 μm.
[0075] Step 4: Deposit the sprayable composite component powder obtained in step 1 on the surface of the bonding layer prepared in step 3 by atmospheric plasma spraying to obtain a double-layer composite component ceramic coating. The preparation parameters of the composite component coating are: spraying distance of 100 mm, powder feeding rate of 14.5 g / min, carrier gas flow rate of 12 SCFH, spraying current of 710 A, spraying voltage of 67 V, main gas flow rate of 52 SCFH, auxiliary gas flow rate of 13 SCFH, and ceramic layer thickness of 180 μm.
[0076] Embodiment 4:
[0077] The difference between this embodiment and embodiment 1 is that the amount of SiC nanopowder used is 5% of the total mass of the sprayable powder. The surface morphology of the coating prepared in this embodiment is as follows: Figure 2 As shown in a) and b) in the figure, the cross-sectional morphology of the coating is as follows Figure 3 As shown in a), b), and c), the XRD spectrum of the coating is as follows Figure 4 shown.
[0078] Embodiment 5:
[0079] The difference between this embodiment and embodiment 1 is that the amount of SiC nanopowder used is 15% of the total mass of the sprayable powder. The surface morphology of the coating prepared in this embodiment is as follows: Figure 2 As shown in e) and f), the cross-sectional morphology of the coating is Figure 3 As shown in g), h), and i), the XRD spectrum of the coating is as follows Figure 4 shown.
[0080] Embodiment 6:
[0081] The difference between this embodiment and embodiment 1 is that the amount of SiC nanopowder used is 20% of the total mass of the sprayable powder. The surface morphology of the coating prepared in this embodiment is as follows: Figure 2 As shown in g) and h), the cross-sectional morphology of the coating is Figure 3 As shown in j), k), and l), the XRD spectrum of the coating is as follows Figure 4 shown.
Claims
1. A self-healing additive / Re2Si2O7 sprayable powder, characterized in that The sprayable powder is made of self-healing additives and Re2Si2O7 as main raw materials and is formed by spray granulation, wherein: the self-healing additive is one or more of Si, MoSi2, SiC, TiC, and Al2O3; the content of the self-healing additive is 1 to 60% of the total mass of the sprayable powder; in the Re2Si2O7, Re is one or more of Y, Yb, Lu, Er, and Sc.
2. A method for preparing the self-healing additive / Re2Si2O7 sprayable powder according to claim 1, characterized in that The method comprises the following steps: Step 1, add deionized water to the ball mill, then add dispersant to the deionized water, after the dispersant is completely dissolved, add nano Re2O3 powder, nano SiO2 powder and self-healing additive according to the designed ratio of Re2Si2O7 and the content of self-healing additive, and ball mill for 6 to 24 hours, then add binder and continue ball milling for 0.5 to 2 hours to obtain a uniform slurry, wherein: the amount of the dispersant is 0.03 to 4% of the total mass of the sprayable powder; the amount of the binder is 0.02 to 15% of the total mass of the sprayable powder; Step 2: After the uniform slurry is spray granulated and solid-phase sintered, a spherical powder is obtained, wherein: the conditions of the solid-phase sintering are: firstly heating to 350°C at a rate of 2-15°C / min and keeping warm for 1-4h, then heating to 1100-1600°C at a rate of 5-20°C / min and keeping warm for 0.5-4h.
3. The method for preparing the self-healing additive / Re2Si2O7 sprayable powder according to claim 2, characterized in that The particle size of the nano Re2O3 powder and nano SiO2 powder is 5-60nm, with a purity of 4N grade; the dispersant is sodium tripolyphosphate, sodium hexametaphosphate, ammonium citrate, sodium citrate 、 One or more of methyl pentanol and polyacrylamide; the adhesive is one of gum arabic, polyvinyl alcohol, polyethylene glycol and epoxy resin; the solid phase sintering is carried out under a protective atmosphere, and the protective atmosphere is one or more of nitrogen, argon and helium; the particle size of the spherical powder is 25 to 100 μm.
4. A nanostructured thermal protective coating resistant to long-term high-temperature oxidation, characterized in that The nanostructured thermal protection coating uses a ceramic-based composite material as a matrix, and a bonding layer and a composite component coating are sprayed on the surface of the matrix in sequence, wherein the material of the composite component coating is the self-healing additive / Re2Si2O7 sprayable powder described in claim 1.
5. The nanostructured thermal protective coating resistant to long-term high-temperature oxidation according to claim 4, characterized in that The ceramic-based composite material is one of silicon carbide structural ceramics and silicon nitride structural ceramics; the material of the bonding layer is one or more of Si, SiC, SiN, MoSi2, Si-HfO2, MoSi2-HfO2, HfSiO4; the thickness of the bonding layer is 50 to 150 μm; the thickness of the composite component coating is 80 to 350 μm.
6. A method for preparing a nanostructured thermal protective coating resistant to long-term high-temperature oxidation according to any one of claims 4 to 5, characterized in that The method comprises the following steps: Step 1: Prepare nanostructured self-healing additive / Re2Si2O7 spherical powder by spray granulation method: Step 1: Add deionized water to a ball mill, then add a dispersant to the deionized water, and after the dispersant is completely dissolved, add nano Re2O3 powder, nano SiO2 powder and self-healing additive according to the designed ratio of Re2Si2O7 and the content of the self-healing additive, and then ball-mill for 6 to 24 hours, and then add a binder and continue to ball-mill for 0.5 to 2 hours to obtain a uniform slurry, wherein: the amount of the dispersant is 0.03 to 4% of the total mass of the sprayable powder; the amount of the binder is 0.02 to 15% of the total mass of the sprayable powder; Step 1 and 2: After the uniform slurry is subjected to spray granulation and solid phase sintering, a spherical powder is obtained, wherein: the conditions of the solid phase sintering are: firstly heating to 350°C at a rate of 2 to 15°C / min and keeping the temperature for 1 to 4 hours, then heating to 1100 to 1600°C at a rate of 5 to 20°C / min and keeping the temperature for 0.5 to 4 hours; Step 2: Using the ceramic-based composite material as the substrate, grinding and polishing the surface to make it smooth and then roughening it, then using ethanol and acetone to ultrasonically clean it, and after drying, using thermal spraying technology to prepare a bonding layer on its surface; Step 3: Using atmospheric plasma spraying technology, the nanostructured self-healing additive / Re2Si2O7 spherical powder obtained in step 1 is deposited on the surface of the bonding layer obtained in step 2 to form a composite component coating.
7. The method for preparing the nanostructured thermal protective coating resistant to long-term high-temperature oxidation according to claim 6, characterized in that The particle size of the nano Re2O3 powder and nano SiO2 powder is 5-60nm, with a purity of 4N grade; the dispersant is sodium tripolyphosphate, sodium hexametaphosphate, ammonium citrate, sodium citrate 、 One or more of methyl pentanol and polyacrylamide; the adhesive is one of gum arabic, polyvinyl alcohol, polyethylene glycol and epoxy resin; the solid phase sintering is carried out under a protective atmosphere, and the protective atmosphere is one or more of nitrogen, argon and helium; the particle size of the spherical powder is 25 to 100 μm.
8. The method for preparing a nanostructured thermal protective coating resistant to long-term high-temperature oxidation according to claim 6, characterized in that The roughening treatment includes one or more of sandblasting, femtosecond laser processing and surface chemical corrosion; the thermal spraying technology is one of atmospheric plasma spraying, low-pressure plasma spraying and supersonic flame spraying.
9. The method for preparing a nanostructured thermal protective coating resistant to long-term high-temperature oxidation according to claim 8, characterized in that When the bonding layer is prepared by atmospheric plasma spraying, the preparation parameters are: spraying distance of 7 to 250 mm, powder feeding rate of 8 to 25 g / min, carrier gas flow rate of 3 to 14 SCFH, spraying current of 450 to 700 A, spraying voltage of 40 to 70 V, main gas flow rate of 25 to 70 SCFH, auxiliary gas flow rate of 2 to 18 SCFH, and spraying speed of 10 to 40 mm / s; when the bonding layer is prepared by supersonic flame spraying, the preparation parameters are: spraying distance of 150 to 500 mm, powder feeding rate of 10 to 50 g / min, carrier gas flow rate of 1 to 8 NLPM, shielding gas flow rate of 150 to 550 NLPM, fuel flow rate of 80 to 350 NLPM, oxygen flow rate of 100 to 400 NLPM, and spraying speed of 20 to 110 mm / s.
10. The method for preparing the nanostructured thermal protective coating resistant to long-term high-temperature oxidation according to claim 6, characterized in that The preparation parameters of the composite component coating are: spraying distance of 60 to 350 mm, powder feeding rate of 5 to 30 g / min, carrier gas flow rate of 4 to 165 CFH, spraying current of 400 to 800 A, spraying voltage of 45 to 80 V, main gas flow rate of 15 to 70 SCFH, and auxiliary gas flow rate of 3 to 20 SCFH; the thickness of the composite component coating is 80 to 350 μm.
Citation Information
Patent Citations
Metallic matrix surface composite coating and preparation method thereof
CN101927586A
Preparation method of crack self-healing ceramic material
CN105272248A
Self-healing environmental barrier coating for ceramic-based composite material and preparation method of self-healing environmental barrier coating
CN113307660A
High-purity nanostructure ytterbium disilicate powder and preparation method thereof
CN115557511A
Long-service-life water-oxygen-corrosion-resistant environmental barrier coating and preparation method thereof
CN118125864A
Cited By
Coating deposition process for implant
CN120366724A
Multi-system powder enhanced thermal protection damping coating and preparation method thereof
CN121379331A
A multi-system powder reinforced thermal protection and vibration damping coating and a method for preparing the same
CN121379331B